Endoscopic Carpal Tunnel Release: Results and Complications in 126 cases. Issue 12 (31st December 2018) - Pereira, Enrique; Argüelles, Santiago; Rodriguez, Martin; Soutullo, Jorge; Santos, Gustavo; Gelo, Melania
Objectives: To report the results and complications of a two portal endoscopic carpal tunnel release (ECTR) with the use of a clear tube for assessing the quality of decompression of the median nerve. Methods: Retrospective analysis of 126 consecutive cases (126 patients) where a two portal ECTR was performed. The demographic and physical examination data were obtained from the medical history. For evaluation, the preoperative and postoperative Quick DASH and the Boston Questionnaire were used and the complications were recorded. Results: The Quick DASH average was 33.7 preoperative (SD 11.05) and 6.8 postoperative (SD 6.44) P<0.001. The Boston Questionnaire´s median average was 1.24 (SD 0.26) for symptoms and 1.18 (SD 0.22) for function. We recorded seven minor complications (5.5%): two cases of transient hypoesthesia and a permanent one of the third web space, three cases of superficial infection, and one case of postoperative neuropathic pain. No major complications or reoperations were documented. Conclusion: Two portal ECTR with the use of a clear tube for assessing the quality of decompression is a safe, effective, predictable and reproducible technique for treatment of idiopathic carpal tunnel syndrome. The complication rate is low when performed by a trained surgeon